Urinary incontinence as a possible signal of neuromuscular toxicity during immune checkpoint inhibitor treatment: Case report and retrospective pharmacovigilance study - Hu, Yizhang; Lu, Wenchao; Tang, Borui; Zhao, Zhixia; An, Zhuoling (Frontiers in Oncology, 2022)
Background Immune checkpoint inhibitors (ICIs) are associated with different immune-related adverse events (irAEs), but there is limited evidence regarding the association between urinary incontinence and ICIs. Methods We described the case of a patient experiencing urinary incontinence who later experienced a series of irAEs such as myocarditis, myositis, and neurologic diseases while on ICI treatment in our hospital. In addition, we queried the Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) from the third quarter of 2010 to the third quarter of 2020 to perform a retrospective study to characterize the clinical features of urinary incontinence associated with ICIs. Result In the FAERS study, 59 cases of ICI-related urinary incontinence were retrieved, and approximately 32.2% of the cases were fatal. Combination therapy with nervous system drugs and age >80 years old were the significant risk factors for fatal outcomes. Among these cases of ICI-related urinary incontinence, 40.7% (n = 24) occurred concomitantly with other adverse events, especially, neurological (fifteen cases), cardiovascular (seven cases), musculoskeletal (six cases), and urological disorders (five cases). Five cases had an overlapping syndrome similar to our case report, including one case of myasthenia gravis with myocarditis and another of myasthenic syndrome with polymyositis. Conclusion ICI-related urinary incontinence might be a signal of fatal neuromuscular irAEs, especially when it occurs concomitantly with ICI-associated neuromuscular–cardiovascular syndrome. Clinicians should be aware of the occurrence of urinary incontinence to identify potentially lethal irAEs in the early phase.